Articles of football published in Sport Mont from 2003 to 2018 - Miomir Maros (Journal of Anthropology of Sport and Physical Education, 2018)
Sport Mont is a scientifi c journal that has existed for 15 years and has so far published about 1000 scientifi c papers. The papers are from various fi elds of sports science - biomechanics, physiology, sports medicine, anthropology, methodology and other fi elds of sports. In this paper, we classifi ed works from the fi eld of football, which were over 200. We also found that the published works had themes - the most contemporary tendencies in sports science. This research can be useful for further theoretical research, as well as for practitioners in the fi eld of football, because they can fi nd a bibliography of this sport in one place.